Blood of empire - McClellan, Brian, 1986- (McClellan, Brian, 1986- Gods of blood and powder, 2019)
"As the final battle approaches a sellsword, a spy, and a general must find unlikely and dangerous allies in order to turn the tides of war in this epic fantasy tale of magic and gunpowder by acclaimed author Brian McClellan"--